2022
DOI: 10.3389/fgene.2022.1068408
|View full text |Cite
|
Sign up to set email alerts
|

Paternal epigenetic influences on placental health and their impacts on offspring development and disease

Abstract: Our efforts to understand the developmental origins of birth defects and disease have primarily focused on maternal exposures and intrauterine stressors. Recently, research into non-genomic mechanisms of inheritance has led to the recognition that epigenetic factors carried in sperm also significantly impact the health of future generations. However, although researchers have described a range of potential epigenetic signals transmitted through sperm, we have yet to obtain a mechanistic understanding of how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 178 publications
1
8
0
Order By: Relevance
“…First, ethnicity is a social concept that can be related to but is fundamentally different from genetic ancestry. Further, if only maternal ethnicity is collected, it ignores the other parent’s contribution to the placental genome and epigenome [ 37 ]. In addition, genetic ancestry is interesting to study in its own right, as it may independently drive DNAme variation and/or confound other associations.…”
Section: Resultsmentioning
confidence: 99%
“…First, ethnicity is a social concept that can be related to but is fundamentally different from genetic ancestry. Further, if only maternal ethnicity is collected, it ignores the other parent’s contribution to the placental genome and epigenome [ 37 ]. In addition, genetic ancestry is interesting to study in its own right, as it may independently drive DNAme variation and/or confound other associations.…”
Section: Resultsmentioning
confidence: 99%
“…As such, one preconception pathway may occur via paternal gene expression which drives placental development, the maternal-fetal interface which is necessary for fetal growth and survival ( Crespi, 2020 ; Dini et al, 2021 ). The field of genomic imprinting has revealed that sperm predominantly controls the growth and differentiation of extraembryonic tissues such as the placenta and yolk sac ( Bhadsavle and Golding, 2022 ). Studies have consistently shown that preconception paternal exposures such as age ( Denomme et al, 2020 ), obesity ( Mitchell et al, 2017 ; Jazwiec et al, 2022 ), toxicants ( Ding et al, 2018 ), cannabis ( Innocenzi et al, 2019 ) and alcohol ( De Cock et al, 2017 ; Thomas et al, 2022 ) result in sex-specific alterations of placental imprinted gene expression, as well as reduced placental weights and disruptions in placental histology.…”
Section: Discussionmentioning
confidence: 99%
“… 37 High-fat diet during early paternal years induces permanent alterations in testicular lipid content and leads to irreversible sperm quality damage, which can persist for up to two generations. 38 , 407 …”
Section: Metabolic Memory and Diseasesmentioning
confidence: 99%